Evaluation of Bond Repair Effect for Ultra-high-strength Concrete Specimens by Neutron Diffraction Method - Yasue, Ayumu; Kobayashi, Kensuke; Yoshioka, Masahiro; Noma, Takashi; Okuno, Koichi; Tanaka, Seiichiro; Hirata, Yoshikazu; Oh-oka, Tokunao; Kimura, Yoshiharu; Nagai, Tomoya; Shobu, Takahisa; Nishio, Yuhei; et al. (Journal of Advanced Concrete Technology, 2023)
The purpose of this study was to evaluate the use of resin injection to repair cracks in ultra-high-strength concrete (UHSC) members. As a preliminary step, the applicability of the neutron diffraction method (NDM) to investigate the effect of repairs in UHSC specimens was examined. The experimental results showed that the NDM can measure stresses in rebars in UHSC and normal concrete specimens. Therefore, in this experiment, the NDM was used to measure the bond performance of repairs with epoxy resin around the slit in normal concrete and UHSC specimens and examine the effect of repair on the UHSC specimens. Displacement around the slit was measured using a PI-shape displacement transducer. The evaluation confirmed that the bond performance of the repaired area was recovered by resin injection regardless of the concrete strength. In addition, the displacement around the slit was smaller for the injected specimens than the non-injected specimens. These experimental results clarified that by injecting resin, the same bond repair effect could be obtained in UHSC and normal concrete specimens.